Brief: the water-energy-food-environment nexus - Dankens, Sarah; Buisson, Marie-Charlotte (International Water Management Institute, 2025)
Water, energy, food, and the environment are deeply interconnected and essential for economic development, environmental sustainability, and human well-being.